The Maturity Model of Data Quality Management in Banking Industry: PT XYZ Core System Customer Data - Rahmad Mulyadi; Yova Ruldeviyani; Noverina Alfiany; Achmad Nizar Hidayanto (Universitas Muhammadiyah Magelang, 2023)
PT XYZ, engaged in the financial industry, has a target to become a leading company in Southeast Asia and has been supported by more than 200 million customer data in its core system. This huge amount of data is expected to create business opportunities, build a risk-aware culture, and increase supremacy in the business strategy of PT XYZ. These things can be achieved if the data used is of good quality data. In fact, found anomalies in a large number of customer data. To get recommendations for improving the quality of customer data, it is necessary to assess the quality of customer data. The customer data quality assessment in this study uses the method introduced by Loshin (2011). Loshin’s Data Quality Management Model (DQMM) adopts a capability maturity level model in building its characteristic matrix. Maturity levels obtained are 3.6 (expectations), 3.6 (dimensions), 4.4 (policy), 3.8 (procedures), 4.2 (governance), 3.8 (standardization), 4, 2 (technology), and 3.8 (performance management). Regarding the expectation that senior management can achieve the highest level of data quality, 9 strategic recommendations were produced 9 strategy recommendations were submitted to PT XYZ is the result of mapping between criteria that have not been met with data quality management activity in Data Management Body of Knowledge (DMBOK) version 2.0. Measurement and monitoring of good data quality is the most influential recommendation for PT XYZ.